Green Tea Extract Ameliorates Ischemia-Induced Retinal Ganglion Cell Degeneration in Rats. (9th July 2019) - Yang, Yaping; Xu, Ciyan; Chen, Yuhong; Liang, Jia-Jian; Xu, Yanxuan; Chen, Shao-Lang; Huang, Shaofen; Yang, Qichen; Cen, Ling-Ping; Pang, Chi Pui; Sun, Xing-huai; Ng, Tsz Kin
Abstract : Purpose . Oxidative stress induced by reduced blood circulation is a critical pathological damage to retinal ganglion cells (RGCs) in glaucoma. We previously showed that green tea extract (GTE) and its catechin constituents alleviate sodium iodate-induced retinal degeneration in rats. Here, we investigated the therapeutic effect of GTE on ischemia-induced RGC degeneration in rats. Methods . RGC degeneration was induced by ischemic reperfusion in adult Fischer F344 rats. Green tea extract (Theaphenon E) was intragastrically administered 4 times within 48 hours after ischemia. RGC survival, pupillary light reflex, expressions of cell apoptosis, oxidative stress, and inflammation-related proteins were studied. Results . Ischemic reperfusion significantly induced apoptotic RGCs, RGC loss, and larger constricted pupil area compared to the untreated normal rats. Expressions of activated caspase-3 and caspase-8, Sod2, and inflammation-related proteins as well as p38 phosphorylation were significantly upregulated in the ischemia-injured rats. Compared to the saline-fed ischemic rats, significantly higher number of surviving RGCs, less apoptotic RGCs, and smaller constricted pupil area were observed in the GTE-fed ischemic rats. GTE also reduced the increased protein expressions caused by ischemic injury but enhanced the Jak phosphorylation in the retina. Notably, green tea extract did not affect the survival of RGCs in the uninjured normal rats. Conclusions . In summary, GTE offers neuroprotection to RGCs under ischemic challenge, suggesting a potential therapeutic strategy for glaucoma and optic neuropathies.